Sinonasal lymphoma: A primer for otolaryngologists. Issue 6 (4th October 2022) - Bitner, Benjamin F.; Htun, Nyein Nyein; Wang, Beverly Y.; Brem, Elizabeth A.; Kuan, Edward C.
Abstract: Objective: Sinonasal lymphomas are a rare entity that commonly present with nonspecific sinonasal symptoms and are often recognized immediately. Through this review, we aim to summarize important principles in diagnosis and treatment of sinonasal lymphomas, with the goal of disseminating the current knowledge of this under‐recognized malignancy to otolaryngologists. Methods: Systemic review using PRISMA guidelines of foundational scholarly articles, guidelines, and trials were reviewed focusing on clinical characteristics of key sinonasal lymphoma subtypes, along with available treatments in the otolaryngology, medical oncology, and radiation oncology literature. Results: Sinonasal lymphoma are derived from clonal proliferation of lymphocytes at various stages of differentiation, of which diffuse large B‐cell lymphoma (DLBCL) and extranodal natural killer/T‐cell lymphoma (ENKTL) are the most common. Diagnosis and staging require biopsy with immunohistochemistry in conjunction with imaging and laboratory studies. Treatment is ever evolving and currently includes multi‐agent chemotherapy and/or radiation therapy. Conclusion: Otolaryngologists may be the first to recognize sinonasal lymphoma, which requires a comprehensive workup and a multidisciplinary team for treatment. Symptoms are nonspecific and similar to many sinonasal pathologies, and it is crucial for otolaryngologists to keep a broad differential. Level of Evidence: 5 Abstract : This review, the authors present a primer for otolaryngologists on the under recognized entity of sinonasal lymphoma. The review covers important topics such as clinical presentation, diagnostic and management strategies, and provide illustrative figures to help readers gain an improved understanding of this disease.